Justice and Reconciliation: The Role of Religious Leaders in Addressing Indonesia’s History of Religious Conflicts (Indonesian Theological Justice Review, 2025)
Indonesia has faced significant religious conflicts, particularly in regions like Maluku and Poso, where sectarian violence has left deep scars on communities. This paper examines the role of religious leaders and institutions in promoting justice and reconciliation in the aftermath of religious conflicts. Focusing on the theological and moral frameworks employed by Islamic, Christian, and interfaith leaders, the study explores how religious teachings have been utilized to foster peacebuilding, forgiveness, and societal healing. The paper reviews key moments of religious conflict and examines the initiatives taken by religious figures to mediate, reconcile, and address historical injustices. It considers the theological basis for reconciliation in Christian and Islamic thought, particularly the teachings of forgiveness, peace, and justice. The paper also investigates the role of religious institutions in supporting post-conflict rehabilitation efforts, such as community dialogues, interfaith collaboration, and advocacy for inclusive justice policies. Ultimately, it highlights the transformative role of theology in promoting long-term peace and societal cohesion, as well as the challenges religious leaders face in navigating political, social, and cultural tensions during times of conflict.